Strategic sectors and employment during the crisis: The case of Andalusia || Sectores estratégicos y empleo durante la crisis: el caso de Andalucía - Campoy-Muñoz, Pilar; Cardenete, Manuel Alejandro; Delgado, M. Carmen (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2015)
The economic crisis has resulted in the shedding of labour characterised by significant differences across the Spanish regions, among which the case of Andalusia stands out. This paper aims to explain the events that occurred between 2005 and 2010, focusing on analysing the region’s productive structure and how it is reflected in its labour market. To do so, a linear SAM model is employed to identify strategic sectors, and their employment trends are then studied through shift-share analysis. The results show the progressive tertiarisation of the Andalusian economy, a regional countercyclical effect that is lower than the national average and sectorial effects on employment in the strategic sectors. || La crisis económica ha generado una destrucción de empleo caracterizada por diferencias significativas en las regiones españolas, destacando el caso de Andalucía. Este trabajo trata de explicar lo ocurrido entre 2005 y 2010, centrándose en el análisis de la estructura productiva regional y cómo ésta se refleja en su mercado laboral. Para ello, se emplea un modelo lineal SAM que identifica los sectores estratégicos, mientras que la evolución del empleo se estudia a través del análisis shift-share. Los resultados muestran la progresiva terciarización de la economía andaluza, un efecto regional contracíclico menor que el detectado a nivel nacional y efectos sectoriales sobre el empleo en los sectores estratégicos andaluces.